2018
DOI: 10.1021/acsphotonics.8b00306
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Enhancement of Two-Photon-Excited Luminescence of Single Quantum Dots by Individual Gold Nanorods

Abstract: Plasmonic enhancement of two-photon-excited fluorescence is not only of fundamental interest but also appealing for many bioimaging and photonic applications. The high peak intensity required for two-photon excitation may cause shape changes in plasmonic nanostructures, as well as transient plasmon broadening. Yet, in this work, we report on strong enhancement of the two-photon-excited photoluminescence of single colloidal quantum dots close to isolated chemically synthesized gold nanorods. Upon resonant excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…Moreover, studies of PL from phosphor 58 and photoconductive phosphor 59 showed a superlinear increase in PL intensity. A quadratic increase of PL intensity have been also observed in quantum dots which exhibit PL emission by two-photon absorption under ultrafast laser excitations 40,60 . In general, the origin of the superlinear PL behavior is closely related to the dynamics of the photoexcited carriers in the nanostructure.…”
Section: Results and Analisismentioning
confidence: 77%
“…Moreover, studies of PL from phosphor 58 and photoconductive phosphor 59 showed a superlinear increase in PL intensity. A quadratic increase of PL intensity have been also observed in quantum dots which exhibit PL emission by two-photon absorption under ultrafast laser excitations 40,60 . In general, the origin of the superlinear PL behavior is closely related to the dynamics of the photoexcited carriers in the nanostructure.…”
Section: Results and Analisismentioning
confidence: 77%
“…Integrating the single-molecule signal for a single peak yields integrated count rates between 0.6 × 10 5 to 8 × 10 6 cts•s −1 (SI Appendix, Fig. S17), exceeding nearly all single-dye molecule and quantum dot count rates reported to date (SI Appendix, Table T2) (19,20,(55)(56)(57)(58)(59)(60)(61)(62)(63). Single-molecule SERS in such an optimized geometry is thus a powerful candidate for single-photon light sources with superior count rates without suffering from blinking or bleaching.…”
Section: Superefficient Plasmonic Nanoarchitectures For Raman Kineticmentioning
confidence: 84%
“…2021, 11, 1375 2 of 13 gap [2]. This enhancement is due to the strong modifications of local fields, that also change the luminescence properties [3][4][5]. The analysis of fine structured electronic-vibrational luminescence spectra is also quite a productive analytical method, but usually at cryogenic conditions [6,7], as well as comparison of data on phonoluminescence and Raman scattering [8].…”
Section: Introductionmentioning
confidence: 99%